Workshop Training to Facilitate Parent-Child Instructional Opportunities for Reading and Social Development with Kindergarten Students. Issue 3 (3rd July 2021) - Wood, Katherine R.; Wood, Eileen; Gottardo, Alexandra; Archer, Karin; Savage, Robert; Piquette, Noëlla
ABSTRACT: This study provided workshops for parents on either early literacy or socio-emotional learning to examine the impact on their children's reading and social skills development (n = 576 parents; n = 584 children). Parents of kindergartners were offered interactive workshops designed to help them identify everyday opportunities to support reading skills or social skills development. Families were randomly assigned by school to workshops on one of three topics: (1) traditional text reading, (2) traditional text reading with computer-assisted learning opportunities, and (3) social-emotional learning. As expected, academic performance improved over time across all conditions. Additional gains were detected on specific language and literacy measures among children in both reading conditions whose parents attended the workshops in comparison to children of parents who did not attend. Gains were observed on academic measures for children in the socio-emotional condition relative to children in the reading conditions. Findings suggest that parental involvement in instructional workshops on early literacy and social development may have significant effects for children's academic success. This study provides evidence for the potential of involving parents in their children's educational interventions as a valuable addition to or alternative to traditional child-directed intervention programs to increase positive outcomes, reduce costs, and enhance parental efficacy.